Barriers and facilitators to care for the terminally ill: A cross-country case comparison study of Canada, England, Germany, and the United States. (February 2014) - Klinger, Christopher A; Howell, Doris; Zakus, David; Deber, Raisa B
Background: Why do many patients not die at their preferred location? Aim: Analyze system-level characteristics influencing the ability to implement best practices in delivering care for terminally ill adults (barriers and facilitators). Design: Cross-country comparison study from a "most similar—most different" perspective, triangulating evidence from a scoping review of the literature, document analyses, and semi-structured key informant interviews. Setting: Case study of Canada, England, Germany, and the United States. Results: While similar with regard to leading causes of death, patient needs, and potential avenues to care, different models of service provision were employed in the four countries studied. Although hospice and palliative care services were generally offered with standard care along the disease continuum and in various settings, and featured common elements such as physical, psycho-social, and spiritual care, outcomes (access, utilization, etc.) varied across jurisdictions. Barriers to best practice service provision included legislative (including jurisdictional), regulatory (e.g. education and training), and financial issues as well as public knowledge and perception ("giving up hope") challenges. Advance care planning, dedicated and stable funding toward hospice and palliative care, including caregiver benefits, population aging, and standards of practice and guidelines to hospice and palliative care, were identified as facilitators. Conclusion: Successful implementation of effective and efficient best practice approaches to care for the terminally ill, such as shared care, requires concerted action to align these system-level characteristics; many factors were identified as being essential but not sufficient. Policy implementation needs to be tailored to the respective health-care system(s), monitored, and fine-tuned.